1991
DOI: 10.1111/j.1432-1033.1991.tb16292.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational change of the haemolymph juvenile‐hormone‐binding protein from Galleria mellonella (L)

Abstract: A juvenile‐hormone‐binding protein (juvenile‐hormone carrier), isolated fromGalleria mellonella haemolymph, was treated with trypsin, chymotrypsin, carboxypeptidase A and subtilisin. Among these enzymes, only subtilisin was able to affect juvenile‐hormone‐binding activity of this protein. With SDS/PAGE it was shown that juvenile‐hormone‐binding protein, a 32‐kDa peptide, is first slowly converted into a 30‐kDa molecule, then into two or three smaller‐molecular‐mass species (20–25 kDa), which in turn were furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…16,20 On the other hand, it has been observed experimentally that G. mellonella JHBP undergoes a profound conformational change upon JH binding, and it has been suggested that such a structural change might have a physiological significance at target cell membrane for hormone signal transmission. 21,22 In this article, we describe the first experimental structure of a lepidopteran JHBP and demonstrate that contrary to the suggested model, it has an elongated shape with a long central α-helix wrapped in a highly curved antiparallel β-sheet, resembling the folding motif found in some mammalian lipidbinding proteins. There is, however, an important difference because at variance with the single-domain JHBP molecule, the boomerang-shaped mammalian lipid-binding proteins are composed of two sequentially connected JHBP-like domains.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…16,20 On the other hand, it has been observed experimentally that G. mellonella JHBP undergoes a profound conformational change upon JH binding, and it has been suggested that such a structural change might have a physiological significance at target cell membrane for hormone signal transmission. 21,22 In this article, we describe the first experimental structure of a lepidopteran JHBP and demonstrate that contrary to the suggested model, it has an elongated shape with a long central α-helix wrapped in a highly curved antiparallel β-sheet, resembling the folding motif found in some mammalian lipidbinding proteins. There is, however, an important difference because at variance with the single-domain JHBP molecule, the boomerang-shaped mammalian lipid-binding proteins are composed of two sequentially connected JHBP-like domains.…”
Section: Introductionmentioning
confidence: 73%
“…The central part of the β-sheet is five-stranded, while near the ends of the helical axis the wrap has only four β-strands, because the edges of the β-sheet structure are disrupted by additional, shorter helices. One such helix (α1) is present near the very N-terminus of the sequence (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), which is spatially adjacent to the C-terminus of helix α4. At the opposite end, two helices (α2, α3) form a right-angle motif, which after another perpendicular kink leads directly to α4.…”
Section: Resultsmentioning
confidence: 99%
“…Correct binding/geometry of ligand inside the protein cavity is not only important for molecular recognition, but also in lead identification. Specific hydrogen bonding and hydrophobic interaction between atoms of ligand and protein leads to dramatic conformational change of JHBP [2,3]. This conformational change is a signal for physiological changes in insect life cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, it resembles the folding pattern of some mammalian lipid-binding proteins. The JHBP molecule undergoes a profound conformational transition upon binding JH [1][2][3][4][5]. This provides a base for rational designing of different analogues of JH.…”
Section: Introductionmentioning
confidence: 99%
“…Galleria mellonella act as severe honey comb pest and is the object of present study [15,16]. Numerous experiments suggested that a conformational change occurs in JHBP of G. mellonella upon JH binding [17,18]. The crystal structure of a JHBP molecule of wax moth, G. mellonella (Gm JHBP; PDB code: 2rck), has been solved showing two binding cavities: W cavity (diameter 6 to 10 Å) and E cavity (diameter 6 to 13 Å) [19].…”
Section: Introductionmentioning
confidence: 98%